Destination image, nostalgic feeling, flow experience and agritourism: An empirical study of Yunling Tea Estate in Anxi, China - Zhang, Sunbowen; Liang, Jingxuan; Ma, Yongqiang; Chen, Youcheng; He, Qiaohua (Frontiers in Psychology, 2022)
This study introduces destination image, nostalgic feeling, and flow experience into tea estate tourism and constructs a theoretical model that includes destination image, nostalgic feeling, flow experience, cultural identity, and tourists’ behavioural intention. Then, an empirical study is conducted with tourists at Yunling Tea Estate in Anxi, China. The results show that all hypotheses are supported except the hypothesis pertaining to the significance of the influence of flow experience on behavioural intention, which is not supported. The model includes eight mediating effects and one moderating effect that is influenced by cultural memory.